Peningkatan Motorik Halus pada Anak melalui Kegiatan Finger Painting - Biri, Leni; Slama, Nurdin (Jambura Early Childhood Education Journal, 2023)
This study aims to determine the impact of finger painting activities on improving fine motor skills in children. The type of research used by researchers is a qualitative research method using classroom action research. The subjects in the research were 10 students of Darma Wanita Onondowa Kindergarten. Data collection techniques through observation, interviews and documentation. From pre-cycle to cycle II, the writer can conclude that through finger painting activities using cassava flour can improve children's fine motor skills in group A Kindergarten Darma Wanita Onondowa, Rampi sub-district. This can be seen from the results of observations which show that the development of children's fine motor skills has changed very well. In the pre-cycle or before the action of research on children who were said to have completed reached 10%, in cycle I the children who had completed reached 30% and in cycle II the children who had completed reached 72.5%.